The Experimental Application of an Occupant Tracking Technology in Domestic Post-Occupancy Evaluation - Holland, Richard (2006)
From 1971 to 2004, the UK population increased by 6.5% to 59.8 million while the number of homes increased by 30% to 24.2 million. Despite this growth, the industry is still accused of delivering homes that are overly expensive, environmentally unsustainable and deficient in number. The wish of the Government is that by 2016 the number of annual new additions in England will have increased by a third to 200,000, though there is little planned to assess how they meet the changing lifestyle needs of consumers.